Disturbing the Peace: The Ghost in beDevil and The Darkside. Issue 5 (3rd September 2017) - Collins, Felicity
ABSTRACT: Comparing transitional and agonistic theories of reconciliation, this essay takes a second look at the figure of the ghost in two films that bookend both the reconciliation movement in Australia and the Blak Wave of film and television production. It argues that telling ghost stories in beDevil (directed by Tracey Moffatt, 1993) and The Darkside (directed by Warwick Thornton, 2013) convenes a space for the unreconciled to disturb the peace in a settlercolonial context where the nation-state is the most recent but not the only polity.